2016
DOI: 10.1002/kin.21011
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Electron Transfer in σ‐Complexation Reactions of 2,6‐Dimethoxy‐3,5‐dinitropyridine with Para‐X‐phenoxide Anions in Aqueous Solution

Abstract: Second-order rate constants have been measured spectrophotometrically for reactions of 2,6-dimethoxy-3,5-dinitropyridine 1 with 4-X-substituted phenoxide anions (X = OMe, Me, H, Cl, and CN) 2a-e in aqueous solution at various temperatures. The effect of phenoxide substituents on the reaction rate was examined quantitatively on the basis of kinetic measurements, leading to nonlinear correlations of ࣔ H and ࣔ S with Hammett's substituent constants (σ ). Each Hammett plots exhibits two intersecting straight lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Large ρ's have been reported in the literature, and they are typical in reactions involving SETs, including the Birch reduction. 43 Further analysis of the data reveals that there is a more satisfactory correlation between the modified Hammett σ p − parameters and the first-order rate constants (Figure 3). 44 This indicates that the resonance contribution has a significant impact on the reaction kinetics as well.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Large ρ's have been reported in the literature, and they are typical in reactions involving SETs, including the Birch reduction. 43 Further analysis of the data reveals that there is a more satisfactory correlation between the modified Hammett σ p − parameters and the first-order rate constants (Figure 3). 44 This indicates that the resonance contribution has a significant impact on the reaction kinetics as well.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…The high and positive reactivity parameter (ρ = 4.8) indicates a strong development of negative charge in the transition state of the degradation reaction, and hence, the more electron donating the substituent is, the slower the degradation reaction. Large ρ’s have been reported in the literature, and they are typical in reactions involving SETs, including the Birch reduction . Further analysis of the data reveals that there is a more satisfactory correlation between the modified Hammett σ p – parameters and the first-order rate constants (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In a series of papers , we have shown that the rate constants k (mol −1 L s −1 ) associated with the σ‐complexation reactions can be classified under the rubric of the original linear‐free energy relationship (LFER) proposed in 1994 by Mayr and co‐workers (Eq. ) , in which E is an electrophilicity parameter, s N is the nucleophile‐specific slope parameter, and N is a parameter characteristic of the given nucleophile in the given solvent and independent of the electrophile:truerightprefixlog0.16emitalick(20C)=sN(E+N)…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of this equation, the electrophilicity parameters E for several neutral electron‐deficient electrophiles, namely nitrobenzofuroxans , nitrotetrazolopyridines , nitrobenzofurazans , nitropyridine , and nitrobenzotriazoles have been quantified and ranked on the comprehensive electrophilicity scale defined for cationic electrophiles by Mayr and co‐workers . We noted that Mayr's approach has also been used to describe the reactivity of S N Ar substrates such as 7‐chloro‐4,6‐dinitrobenzofuroxan and ‐benzofurazan , 1‐X‐2,4‐dinitrobenzenes (X = F, Cl, Br and I) , and 2‐methoxy‐3‐X‐5‐nitrothiophenes (X = SO 2 CH 3 , CO 2 CH 3 , CONH 2 , and H) .…”
Section: Introductionmentioning
confidence: 99%
“…The ρ values are comparable to that reported for reactions, which have been suggested to proceed through a polar σ‐complexation process, for example, ρ = −2.29 for reaction of 3‐cyano‐5‐nitrothiophene with parasubstituted phenoxide anions in aqueous solution at 20°C (Ref. 1) and ρ = −1.84 to −1.75 for reactions of 2,6‐dimethoxy‐3,5‐dinitropyridine with the same series of para‐substituted phenoxide anions in aqueous solution at various temperatures 14 …”
Section: Resultsmentioning
confidence: 99%